2009
DOI: 10.1016/j.joi.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Scientific discovery and topological transitions in collaboration networks

Abstract: Abstract:We analyze the advent and development of eight scientific fields from their inception to maturity and map the evolution of their networks of collaboration over time, measured in terms of co-authorship of scientific papers. We show that as a field develops it undergoes a topological transition in its collaboration structure between a small disconnected graph to a much larger network where a giant connected component of collaboration appears. As a result, the number of edges and nodes in the largest com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 33 publications
(62 reference statements)
8
127
0
3
Order By: Relevance
“…(1), the average degree, k , should obey a simple scaling relation with network size, N , of the form Regardless of the details of the temporal evolution of the field, the number of collaboration (co-authorship) links increases in a scaleinvariant way with the number of authors in the network, as shown in C for nanotechnology and D for sustainability science. These patterns are similar to those we have found in [17] for a variety of smaller scientific fields.…”
Section: From Densification To Percolationsupporting
confidence: 90%
See 4 more Smart Citations
“…(1), the average degree, k , should obey a simple scaling relation with network size, N , of the form Regardless of the details of the temporal evolution of the field, the number of collaboration (co-authorship) links increases in a scaleinvariant way with the number of authors in the network, as shown in C for nanotechnology and D for sustainability science. These patterns are similar to those we have found in [17] for a variety of smaller scientific fields.…”
Section: From Densification To Percolationsupporting
confidence: 90%
“…Second, in our previous study of collaboration networks [17], we found a simple scaling relationship between the number of co-authorship links (or edges) per node, E(t), and the number of authors (nodes), N (t),…”
Section: Characterizing Growth Over Timementioning
confidence: 80%
See 3 more Smart Citations